Respuesta :
Answer:
x = 1 3/11
Step-by-step explanation:
3x( 4x + 7 ) + 3( 8 + 2 ) = 11( 2x + 3 ) + 11
Step 1: Left side do each math in parentheses.
( 12x + 21x ) + ( 24 + 6 ) = 11( 2x + 3 ) + 11
Step 2: Combine like terms on the left side.
33x + 30 = 11( 2x + 3 ) + 11
Step 3: Right side do each math in parentheses.
33x + 30 = 22x + 33 + 11
Step 4: Combine like terms on the right side.
33x + 30 = 22x + 44
Step 5: Subtract lowest non-variable from the highest non-variable
33x = 22x + 14
Step 6: Subtract variable on opposite side you just subtracted non-variable
11x = 14
Step 7: Divide 14 by number multiplied with the variable or just (14/11)
x= 1 3/11
Answer:
[tex]x=\dfrac{1 +\sqrt{673}}{24}, \quad x=\dfrac{1 -\sqrt{673}}{24}[/tex]
Step-by-step explanation:
Given equation:
[tex]3x( 4x +7 ) + 3( 8 + 2 ) = 11( 2x + 3 ) + 11[/tex]
Distribute the parentheses:
[tex]\implies 12x^2+21x+24+6=22x+33+11[/tex]
[tex]\implies 12x^2+21x+30=22x+44[/tex]
Subtract 22x from both sides:
[tex]\implies 12x^2+21x+30-22x=22x+44-22x[/tex]
[tex]\implies 12x^2-x+30=44[/tex]
Subtract 44 from both sides:
[tex]\implies 12x^2-x+30-44=44-44[/tex]
[tex]\implies 12x^2-x-14=0[/tex]
Use the quadratic formula to solve for x.
Quadratic Formula
[tex]x=\dfrac{-b \pm \sqrt{b^2-4ac}}{2a}\quad\textsf{when }\:ax^2+bx+c=0[/tex]
[tex]\implies a=12, \quad b=-1, \quad c=-14[/tex]
Therefore:
[tex]\implies x=\dfrac{-(-1) \pm \sqrt{(-1)^2-4(12)(-14)}}{2(12)}[/tex]
[tex]\implies x=\dfrac{1 \pm \sqrt{1+673}}{24}[/tex]
[tex]\implies x=\dfrac{1 \pm \sqrt{673}}{24}[/tex]